Hydrogen Inhibition of Nitrogen Reduction by Nitrogenase in Isolated Soybean Nodule Bacteroids - Rasche, Madeline E. (1989)
Dihydrogen, a by-product of biological nitrogen fixation, is a competitive inhibitor of N(2) reduction by nitrogenase. To evaluate the significance of H(2) inhibition in vivo, we have measured the apparent inhibition constant for H(2) inhibition of N(2) reduction in Bradyrhizobium japonicum bacteroids isolated from soybean nodules. The rate of N(2) reduction was measured as ammonia production by bacteroids incubated in a buffer containing 200 micromolar leghemoglobin and 10 millimolar succinate under 0.02 atmosphere O(2) and various concentrations of N(2) and H(2). The apparent inhibition constant for H(2) under these conditions was determined to be approximately 0.03 atmosphere. This relatively low value strengthens the proposal that H(2) inhibition of N(2) reduction may be a significant factor in lowering the efficiency of nitrogen fixation in legume nodules.